Pelanggaran Kesepakatan Nuklir Joint Comprehensive Plan of Action Oleh Iran Menurut Hukum Perjanjian Internasional - Nugroho, Dhea Meirani (NOVUM : JURNAL HUKUM, 2021)
International agreements are the main source of international law. International agreements can be made between countries or countries with international organizations or between international organizations. JCPOA was born on July 14, 2015 by Iran alongside with the permanent members of the UN Security Council and Germany as known as P5+1 with the main goal of the peaceful of Iran’s nuclear development. The JCPOA’s parties have such an obligation to comply the provisions contained therein. After the United States withdrawal on May 8, 2018 and re-imposition some of sanctions against Iran by the United States, Iran breached the provision of JCPOA in terms of its uranium development level into 4.5% which is only 3.67% in accordance to Article 28 of JCPOA. Based on that, this study aims to find out what is the status of Iran’s ties to JCPOA and what is the form of sanctions after the breaching of its uranium development level. The research method of this study is using normative juridical and uses data collection techniques using literature study. By conducting an analysis related to the case, it can be concluded that Iran can’t withdraw itself from JCPOA after breaching it. However, if other disadvantaged parties of JCPOA because of this case, they can resolve this case through the Dispute Resolution Mechanism process in accordance to Article 36 and 37 of JCPOA. Sanctions that could be imposed on Iran related to this case is to re-imposition previous-lifted sanctions by the P5+1 before JCPOA.